Answer :
To find the product of the matrices [tex]\(\mathbf{A}\)[/tex] and [tex]\(\mathbf{B}\)[/tex], we need to perform matrix multiplication. Let's denote the matrices as follows:
[tex]\[ \mathbf{A} = \begin{pmatrix} 4 & -2 \\ -3 & 5 \\ 9 & 10 \\ 6 & 11 \end{pmatrix}, \; \mathbf{B} = \begin{pmatrix} 7 \\ -4 \end{pmatrix} \][/tex]
We need to determine the resulting matrix [tex]\(\mathbf{C} = \mathbf{A} \cdot \mathbf{B}\)[/tex]. Matrix [tex]\(\mathbf{C}\)[/tex] will have the same number of rows as [tex]\(\mathbf{A}\)[/tex] and the same number of columns as [tex]\(\mathbf{B}\)[/tex]. Hence, [tex]\(\mathbf{C}\)[/tex] will be a 4x1 matrix.
Perform the multiplication row by row:
1. First row calculation:
[tex]\[ C_{1} = (4 \cdot 7) + (-2 \cdot -4) = 28 + 8 = 36 \][/tex]
2. Second row calculation:
[tex]\[ C_{2} = (-3 \cdot 7) + (5 \cdot -4) = -21 - 20 = -41 \][/tex]
3. Third row calculation:
[tex]\[ C_{3} = (9 \cdot 7) + (10 \cdot -4) = 63 - 40 = 23 \][/tex]
4. Fourth row calculation:
[tex]\[ C_{4} = (6 \cdot 7) + (11 \cdot -4) = 42 - 44 = -2 \][/tex]
By combining all these row results, we obtain the final product matrix [tex]\(\mathbf{C}\)[/tex]:
[tex]\[ \mathbf{C} = \begin{pmatrix} 36 \\ -41 \\ 23 \\ -2 \end{pmatrix} \][/tex]
Thus, the product of the given matrices [tex]\(\mathbf{A}\)[/tex] and [tex]\(\mathbf{B}\)[/tex] is:
[tex]\[ \left[\begin{array}{cc} 4 & -2 \\ -3 & 5 \\ 9 & 10 \\ 6 & 11 \end{array}\right]\left[\begin{array}{c} 7 \\ -4 \end{array}\right] = \left[\begin{array}{c} 36 \\ -41 \\ 23 \\ -2 \end{array}\right] \][/tex]
[tex]\[ \mathbf{A} = \begin{pmatrix} 4 & -2 \\ -3 & 5 \\ 9 & 10 \\ 6 & 11 \end{pmatrix}, \; \mathbf{B} = \begin{pmatrix} 7 \\ -4 \end{pmatrix} \][/tex]
We need to determine the resulting matrix [tex]\(\mathbf{C} = \mathbf{A} \cdot \mathbf{B}\)[/tex]. Matrix [tex]\(\mathbf{C}\)[/tex] will have the same number of rows as [tex]\(\mathbf{A}\)[/tex] and the same number of columns as [tex]\(\mathbf{B}\)[/tex]. Hence, [tex]\(\mathbf{C}\)[/tex] will be a 4x1 matrix.
Perform the multiplication row by row:
1. First row calculation:
[tex]\[ C_{1} = (4 \cdot 7) + (-2 \cdot -4) = 28 + 8 = 36 \][/tex]
2. Second row calculation:
[tex]\[ C_{2} = (-3 \cdot 7) + (5 \cdot -4) = -21 - 20 = -41 \][/tex]
3. Third row calculation:
[tex]\[ C_{3} = (9 \cdot 7) + (10 \cdot -4) = 63 - 40 = 23 \][/tex]
4. Fourth row calculation:
[tex]\[ C_{4} = (6 \cdot 7) + (11 \cdot -4) = 42 - 44 = -2 \][/tex]
By combining all these row results, we obtain the final product matrix [tex]\(\mathbf{C}\)[/tex]:
[tex]\[ \mathbf{C} = \begin{pmatrix} 36 \\ -41 \\ 23 \\ -2 \end{pmatrix} \][/tex]
Thus, the product of the given matrices [tex]\(\mathbf{A}\)[/tex] and [tex]\(\mathbf{B}\)[/tex] is:
[tex]\[ \left[\begin{array}{cc} 4 & -2 \\ -3 & 5 \\ 9 & 10 \\ 6 & 11 \end{array}\right]\left[\begin{array}{c} 7 \\ -4 \end{array}\right] = \left[\begin{array}{c} 36 \\ -41 \\ 23 \\ -2 \end{array}\right] \][/tex]